Determinants of Mental Health Care Utilization in a Suicide High-risk Group With Suicidal Ideation - Hyun-Soo Kim; Moo-Sik Lee; Jee-Young Hong (Korean Society for Preventive Medicine, 2016)
Objectives: The suicide rate in Korea is increasing every year, and is the highest among the Organization for Economic Cooperation and Development countries. Psychiatric patients in particular have a higher risk of suicide than other patients. This study was performed to evaluate determinants of mental health care utilization among individuals at high risk for suicide. Methods: Korea Health Panel data from 2009 to 2011 were used. Subjects were individuals at high risk of suicide who had suicidal ideation, a past history of psychiatric illness, or had utilized outpatient services for a psychiatric disorder associated with suicidal ideation within the past year. The chi-square test and hierarchical logistic regression were used to identify significant determinants of mental health care utilization. Results: The total number of subjects with complete data on the variables in our model was 989. Individuals suffering from three or more chronic diseases used mental health care more frequently. Mental health care utilization was higher in subjects who had middle or high levels of educational attainment, were receiving Medical Aid, or had a large family size. Conclusions: It is important to control risk factors in high-risk groups as part of suicide prevention strategies. The clinical approach, which includes community-based intervention, entails the management of reduction of suicidal risk. Our study identified demographic characteristics that have a significant impact on mental health care utilization and should be considered in the development of suicide prevention strategies. Further studies should examine the effect of mental health care utilization on reducing suicidal ideation.